Melastomataceae of the Sierra Nevada de Santa Marta (Colombia): floristic affinities and annotated catalogue - Alvear, Marcela; Ocampo, Gilberto; Parra-O., Carlos; Carbonó, Eduino; Almeda, Frank (Phytotaxa, 2015)
The Sierra Nevada de Santa Marta (SNSM), the world’s highest coastal mountain range, has long been recognized for its high levels of biological diversity and endemism but no exhaustive inventory of the flora exists today. Here we present an annotated catalogue of the angiosperm family Melastomataceae from this diverse massif. The annotated species list is based largely on the treatment of Melastomataceae for the forthcoming Catalogue of the Plants of Colombia together with several floristic data sources, confirmed specimen records held in different herbaria, and recent field work. The catalogue of Melastomataceae presented here includes 20 genera and 86 species, 21 of which are endemic to Colombia and 15 of those are endemic to the SNSM. We also include floristic similarity analyses to compare the species of Melastomataceae from the SNSM with those from other Colombian biogeographic regions and other Neotropical countries or regions.